INTERNALISASI KARAKTER ‘UMAR IBN ‘ABD AL ‘AZIZ SEBAGAI PEMIMPIN UMAT ISLAM DAN PENGARUHNYA PADA PEMERINTAHAN DAWLAH BANI UMAYYAH SUATU TINJAUAN SEJARAH ISLAM - Fatmawati, Fatmawati (State Institute for Islamic Studies Batusangkar, 2017)
This paper aims to internalize the character of the Caliph Umar bin Abdul Aziz as the leader of Muslims and its influence on the government of Dawlah Bani Umayyah, and to describe the wisdom of Umar ibn 'Abd al' Aziz in the field of religion, economy and social society. In this paper will be discussed about the Character 'Umar as the leader of Muslims related to religious matters, related to economic issues, and related to social issues. The research that the authors carried out was literature research, which relates to Karater Umar ibn 'Abd al' Aziz as the leader of Muslims and its influence on the Dawlah Bani Umayyah government in Historical reviews. The method that writer use in research is by approach of content analysis (content rate, that is research which is deep discussion to content of written or printed information either in book form or other with qualitative approach). The results show that the character of 'Umar ibn' Abd al 'Aziz in the field of religion, Pengkodifikasian hadis officially done during the reign of' Umar ibn 'Abd al' Aziz,. Umar ibn Abd Aziz always discipline in establishing the prayer that he built as beautiful as possible with all the solemnity and kekhusu'an according to the way the Prophet performed his prayer. In the economic field, 'Umar stopped tax collection from newly converted Christians, so the Christians converted to Islam. Poverty, poverty has been overcome during the reign of this caliph, it may be said that those who want to spend zakat difficult to get the people who are entitled to receive it. In the social field, Generalize the status between Arabs and non-Arab Muslim groups known as mawali. 'Umar ibn' Abd al 'Aziz also ordered to stop the condemnation of Ali in the pulpits of Friday.